A Critical Discourse Analysis of Body Positivity and Female Sexuality Narratives on Social Media - Alfiansyah, Pandu; Martina, Hanna Shasyi; Rahma, Afifa Siti; Safitri, Dini (Kalijaga Journal of Communication, 2025)
This research examines critical discourse surrounding body positivity and women's sexuality on social media, with a focus on the Instagram account @ririebogar. The account was chosen because it has a significant influence on shaping the body positivity discourse among young women in Indonesia and actively discusses issues related to sexuality. Utilizing Fairclough's Critical Discourse Analysis framework, this study aims to examine how these narratives reflect, negotiate, and contest dominant norms related to body and sexuality in Indonesia. Data was collected from 25 posts during the period from January to December 2024, employing an in-depth qualitative approach. The findings suggest that this account actively challenges traditional beauty standards that often harm women, promoting self-acceptance through strong affirmative language and engaging visual representations. Text analysis reveals deliberate lexical choices that sharply contrast normative narratives with the transformative narratives offered by this account. The identified discursive practices demonstrate structured content production strategies that effectively leverage the mechanisms and features of digital platforms. However, this research also reveals the complexities that arise between empowerment and commodification in the context of evolving digital capitalism. Overall, this study contributes to a deeper understanding of the role of social media as both a space of resistance and an arena for the reproduction of hegemonic ideologies related to women's bodies and sexuality. This research is expected to provide new insights and a more comprehensive understanding of the dynamic relationship between social media, body culture, and women's sexuality in Indonesia.